2019
DOI: 10.1146/annurev-micro-020518-120235
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Cascades Governing Entry into and Exit from Host Cells by Toxoplasma gondii

Abstract: The Apicomplexa phylum includes a large group of obligate intracellular protozoan parasites responsible for important diseases in humans and animals. Toxoplasma gondii is a widespread parasite with considerable versatility, and it is capable of infecting virtually any warm-blooded animal, including humans. This outstanding success can be attributed at least in part to an efficient and continuous sensing of the environment, with a ready-to-adapt strategy. This review updates the current understanding of the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 145 publications
1
60
0
Order By: Relevance
“… Toxoplasma gondii and Plasmodium falciparum belong to the phylum of Apicomplexa that groups numerous parasites which are responsible for severe diseases in humans and animals. These parasites are highly polarized cells that harbor an apical complex composed of specialized secretory organelles called micronemes and rhoptries ( 5 ) that participate in motility, invasion and egress from infected cells, as well as modulation of host cellular responses ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“… Toxoplasma gondii and Plasmodium falciparum belong to the phylum of Apicomplexa that groups numerous parasites which are responsible for severe diseases in humans and animals. These parasites are highly polarized cells that harbor an apical complex composed of specialized secretory organelles called micronemes and rhoptries ( 5 ) that participate in motility, invasion and egress from infected cells, as well as modulation of host cellular responses ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different microorganisms sense the host environment to trigger molecules and signaling cascades, that ensure an efficient infection and survival within host cells [25][26][27][28] . For instance, Toxoplasma gondii efficiently senses the environment to regulate the exocytosis of its Microneme, which crucially participates in the egress, gliding motility and invasion during the parasite lytic cycle 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Different microorganisms sense the host environment to trigger molecules and signaling cascades, that ensure an efficient infection and survival within host cells [25][26][27][28] . For instance, Toxoplasma gondii efficiently senses the environment to regulate the exocytosis of its Microneme, which crucially participates in the egress, gliding motility and invasion during the parasite lytic cycle 26 . In addition to its function in motility, the trypanosome flagellum appears to serve as a sensory organelle that could regulate parasite virulence, motility and cell-to-cell communication, among other processes [29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Egress from the host cell is an essential step for the infection cycle of T. gondii. During egress, parasites will leave a likely dying and exhausted host cell and will search for a new one to invade and start a new lytic cycle [31]. It was shown that parasites growing in vitro in tissue cultures responded to the addition of ionophores by promptly egressing [10].…”
Section: Discussionmentioning
confidence: 99%